The Effectiveness of the Guided Inquiry Learning Model with the help of a Virtual Laboratory to Increase Students' Concept Mastery in Acid-Base Material - Sella Ramadhila; Emmawaty Sofya; Tasfiri Efkar (Jurnal Pendidikan dan Pembelajaran Kimia, 2022)
This research was conducted using Non-Equivalent (Pretest-Postest) Control Group Design with the aim of describe the effectiveness of the guided inquiry learning model with the help of a virtual laboratory in improving students' mastery of concepts in acid-base material. The sample was taken by using purposive sampling technique and  the population is from all students in grade XI MIPA SMA Negeri 14 Bandar Lampung for 2021/2022 academic year and it was obtained the XI MIPA 1 as the control class and XI MIPA 2 as the experimental class. The results showed that the average n-Gain of students' conceptual mastery for the control class was 0.63 with ‘medium’ criteria and the experimental class was 0.72 with ‘high’ criteria. Based on the two-average difference test that has been carried out, the results of hypothesis testing obtained information that the average value of the n-Gain value of students' conceptual mastery in acid-base material in the experimental class was higher than the average value of the n-Gain value of students' conceptual mastery in the experimental class so that it can be concluded that the guided inquiry learning model with the help of a virtual laboratory in acid-base material can improve students' mastery of concepts. Keywords: guided inquiry, virtual laboratory, concept mastery, acid-base